2001
DOI: 10.1177/089686080102100203
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Advanced Glycation End-Products and Aminoguanidine on Tnfα Production by Rat Peritoneal Macrophages

Abstract: Objective To evaluate the effect of advanced glycation end-products (AGEs) and the inhibitor of their formation, aminoguanidine, on tumor necrosis factor-α (TNFα) production (as a functional marker) by rat peritoneal macrophages (PMΦ). Design Charles River rats underwent a daily intraperitoneal injection of peritoneal dialysis solution [(PDS), 4.25 g/dL dextrose; Dialine, Travenol, Ashdod, Israel] for a 2-month period (group E). Another group of rats was subjected to the same protocol with the addition of 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Rojas et al have reported nitric oxide synthase induction by AGEs in activated murine macrophages [39]. We have recently shown increased TNF-a production by LPS stimulated rat peritoneal macrophages in response to AGE-BSA [40]. It thus appears that AGEs, on the whole, activate the immune cell response, certainly in its resting state.…”
Section: Discussionmentioning
confidence: 67%
“…Rojas et al have reported nitric oxide synthase induction by AGEs in activated murine macrophages [39]. We have recently shown increased TNF-a production by LPS stimulated rat peritoneal macrophages in response to AGE-BSA [40]. It thus appears that AGEs, on the whole, activate the immune cell response, certainly in its resting state.…”
Section: Discussionmentioning
confidence: 67%
“…They injected peritoneal dialysis solution and AG for 2 months in different groups of rats and concluded beneficial role of AG on rat peritoneum. 29 Ara et al also studied protective effect of AG against oxidative stress in an experimental peritoneal adhesion model in rats and concluded that intraperitoneal administration of AG decreases the incidence and extent of peritoneal adhesions and causes a decrease in malondialdehyde, total nitrite/nitrate, and reduced glutathione. 30 But use of NOS inhibitors is not without its hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Each 100 mL elute was collected, concentrated, and freeze-dried for further assay of antioxidant activities, α-iphenyl-β-picryl-hydrazyl (DPPH) scavenge, and lipid peroxidation inhibition. Fractions of 7,8,23,39,40,42,43,44,45, and 46, which showed high activity either on DPPH scavenge or lipid peroxidation inhibition, were combined and recrystallized, and then identified by 13C NMR.…”
Section: Protein Concentration Analysismentioning
confidence: 99%
“…TNF-α activation may induce apoptosis of renal cells, abnormal blood flow, and tubulointerstitial fibrosis, which result in glomerular damage (37). ROS promotes the production of TNF-α in renal mesangial cells, and AGEs also stimulate NO, ROS, TNFα, and IL-1 secretion from macrophages, which cause inflammation and subsequent renal damage (5,(38)(39)(40).…”
Section: Nrbe Modulated Renal Inflammation Of Diabetic Ratsmentioning
confidence: 99%